Amblyopia update: new treatments. Issue 5 (September 2016) - Vagge, Aldo; Nelson, Leonard B.
Abstract : Purpose of review: This review article is an update on the current treatments for amblyopia. In particular, the authors focus on the concepts of brain plasticity and their implications for novel treatment strategies for both children and adults affected by amblyopia. Recent findings: A variety of strategies has been developed to treat amblyopia in children and adults. New evidence on the pathogenesis of amblyopia has been obtained both in animal models and in clinical trials. Mainly, these studies have challenged the classical concept that amblyopia becomes untreatable after the 'end' of the sensitive or critical period of visual development, because of a lack of sufficient plasticity in the adult brain. Summary: New treatments for amblyopia in children and adults are desirable and should be encouraged. However, further studies should be completed before such therapies are widely accepted into clinical practice.